Implementation of slow magnetic relaxation in a SIM-MOF through a structural rearrangement12. Issue 41 (4th October 2018) - Castells-Gil, Javier; Baldoví, José J.; Martí-Gastaldo, Carlos; Mínguez Espallargas, Guillermo
Abstract : Dehydration of a Dy-based MOF causes the appearance of slow-magnetic relaxation due to the changes of the charge density of the coordination environment. Abstract : Here we report the structural flexibility of a Dy-based single-ion magnet MOF in which its magnetic properties can be modified through a ligand substitution process involving an increase of the charge density of the coordination environment.